2015
DOI: 10.1111/spc3.12198
|View full text |Cite
|
Sign up to set email alerts
|

American Indian health disparities: psychosocial influences

Abstract: The American Indian (AI) population suffers from significant health disparities. Death rates from diabetes, cancer, infant mortality, and other causes are higher among AIs. Numerous psychosocial influences, including a history of genocide and boarding school experiences, have led to unresolved historical trauma and its associated poor health outcomes. Adverse childhood experiences are also a strong predictor of risk for numerous chronic and behavioral health conditions. Food programs for impoverished populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 52 publications
0
79
0
Order By: Relevance
“…Prior research has shown an association between the pre-existing conditions now associated with increased Coronavirus risk. Since the incidence of these pre-existing conditions are disproportionately high among people of color, in particular obesity, diabetes, cardiovascular disease, and chronic illness(6)(7)(8)(9)(10)(11)(12)(13)(14)(115)(116)(117)(118)(119), it is not surprising that our study demonstrated an association between the number of Coronavirus health risks and mental health indices. Of note, is that 28% and 22% of our participants identified as sexual or gender minorities, respectively.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Prior research has shown an association between the pre-existing conditions now associated with increased Coronavirus risk. Since the incidence of these pre-existing conditions are disproportionately high among people of color, in particular obesity, diabetes, cardiovascular disease, and chronic illness(6)(7)(8)(9)(10)(11)(12)(13)(14)(115)(116)(117)(118)(119), it is not surprising that our study demonstrated an association between the number of Coronavirus health risks and mental health indices. Of note, is that 28% and 22% of our participants identified as sexual or gender minorities, respectively.…”
mentioning
confidence: 61%
“…Intergenerational trauma created by American slavery, colonialism, Jim Crow laws, and segregation, has been shown to effect both physical and psychological health among Black people (62)(63)(64). Loss and violation of sacred lands and a history of segregation of American Indian boarding schools and food programs is a significant stressor for Indigenous persons (12,65). For Latinx people, studies have found significant association among documentation status (66,67), fear of deportation (68), acculturation stress (69)(70)(71), and mental health status.…”
Section: The Relationship Between Racial/ethnic Discrimination and Symentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there has been a recent push with somewhat more acceptance in certain conventional medical settings towards supporting traditional Indigenous medicine interventions as demonstrated in some of the literature in this scoping review; however, the question remains whether or not “these efforts tend to represent political achievements more so than bona fide epistemological reconciliation” [ 72 ]. With continuing and significant health disparities existing in Indigenous populations in North America [ 102 ], a broader concerted effort needs to be mobilized and operationalized to ensure that Indigenous self-determined ways of knowing in relation to health and delivery of care is prioritized. Initial outcomes are promising in regard to traditional medicine’s benefit for Indigenous peoples in self-determined healthcare environments and settings.…”
Section: Discussionmentioning
confidence: 99%
“…Donald Warne and Denise Lajimodiere explain that the trauma experienced by Native peoples at the hands of Europeans has left wounds that go to the spiritual soul of a people and to the lands on which they live (Warne and Lajimodiere , 572). The cartography of trauma maps the relationships between family, genetics, and the land.…”
Section: Embodied and Extended Cognition: The “Where” Of Our Bodyselvesmentioning
confidence: 99%